Reporting radiographer peer review systems: A cross-sectional survey of London NHS Trusts. Issue 1 (February 2021) - Woznitza, N.; Steele, R.; Hussain, A.; Gower, S.; Groombridge, H.; Togher, D.; Lofton, L.; Lainchbury, J.; Compton, E.; Rowe, S.; Robertson, K.
Abstract: Introduction: Peer review is frequently incorporated within radiographer reporting services. The aim of this study is to establish peer review systems used for radiograph reports provided by reporting radiographers in London. Methods: An online cross-sectional survey of NHS diagnostic imaging departments was performed. Reporting radiographer demographics (number, frequency of reporting, scope of practice) and systems used to provide peer review of radiograph reports (review frequency, case selection, volume, outcome measure, practitioner performing the review) were collected. Results: Thirteen eligible responses were received (61.9% response rate). Variability was found between Trusts in the number of reporting radiographers, frequency of reporting sessions and scope of practice. Most Trusts (9 of 13, 69.2%) have active peer review systems for radiographer reporting. All peer review systems use random case selection, most often performed on a monthly basis. Both a fixed number or a percentage of cases reported were used, with true positive, true negative, false positive, false negative the most frequent outcome measure. Of the 12 Trusts that have or are planning a peer system, all currently or plan to use reporting radiographers to conduct the review, with five (41.2%) also using consultant radiologists. Conclusion: Peer review of radiographer reporting is common in London NHS Trusts although there is variation in the methods used. Implications for practice: Radiographer reports frequently undergo peer review. Standardisation of reporting radiographer peer review systems should be considered, and a standardised systematic peer review system has been proposed.